EFFECT OF DIFFERENT TYPES OF SLEEP DEPRIVATION AND SLEEP RECOVERY ON SALIVARY PH - Handayani, Fani Tuti; Widyaningsih, Pratiwi Nur; Arjadi, Fitranto (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: Salivary pH can rise or fall influenced by intrinsic and extrinsic factors. Sleep deprivation is one example of intrinsic factors. Sleep deprivation causes a reduction in sleep time at a certain time. Purpose: Analyze the effect of different types of sleep deprivations and sleep recovery on salivary pH. Method: This study was experimental research with a post-test only with a control group design. Thirty white Wistar strain rats were randomly divided into 5 groups: healthy control group (KI), partial sleep deprivation (PSD/KII), total sleep deprivation (TSD/KIII), partial sleep deprivation, and continued sleep recovery (PSD+SR/KIV) and total sleep deprivation and continued sleep recovery (TSD+SR/KV). The treatment is carried out on a single platform method. Salivary pH was measured with the help of color-coded pH strips that were given grading after the completion of sleep deprivation induction. Result: The mean decrease in salivary pH was highest in the TSD group. One Way ANOVA test showed significant differences (p <0.05) in the control group with PSD and TSD, the PSD group with PSD+SR, TSD group with PSD+SR and TSD+SR. Conclusion: Sleep deprivation is proven to reduce the pH of Saliva. Total sleep deprivation is a chronic condition that has the most influence on decreasing salivary pH. The effect of decreasing salivary pH due to sleep deprivation is proven to be overcome by sleep recovery.